EFFECT OF THE LEARNING OUTCOMES OF THE TERRESTIAL NAVIGATION COURSE IN COMPETENCE PASSAGE PLANNING FOR CADETS WHO ARE CARRYING OUT SEA PROJECT ON BOARD - Rispa Saeful Mu'tamar; Dedy Kurniadi; Fazri Hermanto (Berajah Journal, 2023)
Terrestial Navigation is a harmonious union between science and art that teaches us how to sail a ship from one place to another safely, quickly, efficiently, and economically and safely to the destination. Passage Planning is the planning of ship voyages from one place to another safely, quickly and economically, and safely to the destination. Shipping from one port to another must be coordinated by all crew members. Politeknik Pelayaran Malahayati, which is a Technical Implementation Unit under the Ministry of Transportation, the Transportation HR Development Agency, which has the task of implementing Vocational Education, research, and Community Service in the field of Shipping, has organized a Diploma III Nautical Studies, Ship Engineering Studies, and Ship Electrical System Studies. This study aims to evaluate the influence of understanding Passage Planning Terrestial Navigation on the competence of cadets when doing Sea Project on board. The research method used is quantitative research with a sampling technique using purposive sampling on cadets at Voyage schools. Data was collected through questionnaires and regression analysis was used to test the hypothesis. The results of the study show that the understanding of Passage Planning in Terrestial Navigation has a significant effect on the competence of cadets when carrying out maritime practices on board. Therefore, it is suggested for Voyage schools improve the learning of Terrestial Navigation Passage Planning to increase the competence of cadets in carrying out maritime practices on board. The results of the study simultaneously obtained the value of Fcount > Ftable [29.008 > 2.513] at the significance level∝ = 5%, this states that simultaneously the variables Catalog & Nautical Chart (x1), Plotting Position (x2), Distance and Course Voyage Determination (x3), Voyage Planning Tabulation (x4), affect competence cadets during Sea Project on board at Politeknik Pelayaran Malahayati.